Polio Eradication Efforts in Nepal - Suvedi, BK (Journal of Nepal Paediatric Society, 2009)
<!–[if gte mso 9]> mother 11.6568 <![endif]–><!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Nepal has made tremendous effort for polio eradication. The efforts are based on the global polio eradication strategies. Despite all the efforts as per the global strategies, wild poliovirus is still present in the country. The importance of water, hygiene and sanitation is stressed as an additional strategy in still persisting areas. Key words: Poliomyelitis, Eradication, Nepal, Immunization, Surveillance. doi:10.3126/jnps.v27i2.1409 J. Nepal Paediatr. Soc. Vol.27(2) p.57-59